The association of maternal diabetes with attention deficit and hyperactivity disorder in offspring: a meta-analysis - Zhao L (Dove Medical Press, 2019)
Lifeng Zhao,1 Xuesong Li,2 Guanying Liu,1 Baoling Han,1 Jian Wang,1 Xia Jiang1 1Department of Endocrinology, Tianjin First Center Hospital, Tianjin, China; 2First Center Clinical Medical Institute, Tianjin Medical University, Tianjin, China Objective: Recent controversial evidence suggests that maternal diabetes may increase the risk of attention deficit and hyperactivity disorder (ADHD) in offspring. To examine this potential association, a systematic literature search and meta-analysis was performed. Methods: OR or risk ratio (RR) from each study was obtained and combined for evaluating the risk. Six cohort studies and three case-control studies were included in the present study. Results: The meta-analysis of the highly heterogeneous case-control studies did not find significant association between maternal diabetes and ADHD risk (OR: 1.20, 95% CI: 0.96–1.49). The combining of the cohort studies demonstrated that offspring of diabetic mothers were at higher risk of ADHD (RR: 1.40, 95% CI: 1.27–1.54); however, publication bias was identified. When exposure was specified as gestational diabetes mellitus (GDM), GDM exposure increased the risk of ADHD for children by 164% (95% CI: 1.25–5.56) in a Caucasian population. Neither heterogeneity nor publication bias was detected. Conclusion: Maternal diabetes, especially GDM, is probably a risk factor for ADHD in the Caucasian population. More studies based on large sample size and different ethnicities are needed to confirm this association. Keywords: maternal diabetes, attention deficit hyperactivity disorder, meta-analysis